Kimberlites in the Slave Craton, Northwest Territories, Canada - Pell, J. (Geoscience Canada, 1997)
Summary A significant new kimberlite province, which hosts more than 150 kimberlite pipes and is centred in the heart of the Archean Slave Province, was discovered in 1991. By early 1998 Canada's first diamond mine is expected to be in production from this new kimberlite province. The principal diamond-bearing pipes occur in the Lac de Gras region, east-central Slave Province. Preliminary radiometric age determinations indicate that these pipes were emplaced in Late Cretaceous and Eocene time. Outside of the Lac de Grasarea. Middle Jurassic-, Late Ordovician-, and Cambrian-aged kimberlites have been discovered, some of which also have good economic potential. The study of kimberlites in the Slave Province is at avery early stage and as work continues, a better understanding of their ages, pe-trology, and diamond potential will be gained. This paper summarizes what is known to date.